Inovações na produção de antibióticos β-lactâmicos - Rodrigues, Dasciana de Sousa (Universidade Federal de São Carlos, 2009)
The industrial production of 6-APA includes: (1) cultivation of Penicillium chrysogenum; (2) extraction with organic solvents, (3) crystallization; (4) penicillin hydrolysis by immobilized penicillin acylase; (5) extraction of phenyl acetic acid (AFA); (6) precipitation of 6-APA at its isoelectric point ( pH ~ 3,6). The scientific community and industry have interest in reducing the number of process steps required for 6-APA production. In this thesis a new method for 6-APA production is presented. In this process, the simultaneous production and hydrolysis of penicillin was carried out. The 6-APA was extracted from culture broth using ionic adsorbent. To demonstrate the technical viability of the process a suitable biocatalysts to perform the hydrolysis of penicillin in the complex media has been developed. The enzymatic extract, containing PGA was partially purified by affinity adsorption on agarose-tryptophan, it was necessary to prepare the biocatalyst. The apparent purification factor obtained was 4,5 and purified PGA was immobilized on agaroseglyoxil by multipoint covalent attachment. The biocatalysts obtained show stability under conditions of sterilization and application in bioreactor. However, their mechanical stability under vigorous conditions of agitation used in stirred tank bioreactors was not satisfactory. Three strategies were used to avoid fragmentation of the biocatalyst. The first strategy was to involve the impellers with a helicoidal structure. In this system the biocatalyst was maintained under agitation in external bulk of the apparatus. In the second strategy, the biocatalyst was introduced into the bioreactor as the biomass density reached a maximum, in this case, the cultivation was carried out under constant agitation speed (300 rpm). An airlift bioreactor was used as third strategy to maintain the pellet structure. These systems were efficient in increasing medium agitation without destroying the pellets. Complete hydrolysis of penicillin (30 g / L) was obtained after five days of cultivation and extraction of 6-APA on ionic exchanger was investigated. The extraction of 6-APA by ionic interaction using chitosan modified with glutaraldehyde and arginine is a good method for recovery it. However, optimization in this method is necessary to achieve the recovery of 6-APA at satisfactory levels for the pharmaceutical industry. The new method for production of 6-APA shows that is possible to eliminate the use of organic solvents and to reduce the number of process steps.
Keywords: Biotecnologia; Penicilina G acilase; Enzimas - purificação; Imobilização; Ácido 6-aminopenicilânico; Adsorção; Interação iônica; Penicillin G acylase; Purification; Immobilization; Penicillin; Hydrolysis; 6- aminopenicillanic acid; Ddsorption; Ionic interaction; ENGENHARIAS::ENGENHARIA QUIMICA